Changes of dietary fat and carbohydrate content alter central and peripheral clock in humans - Pivovarova-Ramich, Olga; Jürchott, Karsten; Rudovich, Natalia; Hornemann, Silke; Ye, Lu; Möckel, Simona; Murahovschi, Veronica; Kessler, Katharina; Seltmann, Anne-Cathrin; Maser-Gluth, Christiane; Mazuch, Jeannine; Kruse, Michael; et al. (The journal of clinical endocrinology & metabolism, 2015)
Context:. The circadian clock coordinates numerous metabolic processes with light-dark and feeding regimens. However, in humans it is unknown whether dietary p